Antibacterial electrospun PVA/Enzymatic synthesized poly(catechol) nanofibrous mid-layer membrane for ultrafiltration - Coelho, Dora (2017)
Two different nanofibrous antibacterial membranes containing enzymatically synthesized poly(catechol) (PC) or silver nitrate (AgNO3, positive control) blended with poly(vinyl alcohol) (PVA) and electrospun onto a poly(vinylidene fluoride) (PVDF) basal disc to generate thin-film composite mid-layers were produced for water ultrafiltration applications. The developed membranes were thoroughly characterized in terms of morphology, chemical composition and general mechanical and thermal features, antimicrobial activity and ultrafiltration capabilities. The electrospun blends were recognized as homogeneous. Data revealed relevant conformational changes in the PVA side groups, attributed to hydrogen bonding, and high thermal stability and residual mass. PVDF+PVA/AgNO3 membrane displayed 100% growth inhibition of both Gram-positive and Gram-negative bacteria strains, despite the wide range of fiber diameters generated, from 24 to 125 nm, formation of numerous beads and irregular morphology. The PVDF+PVA/PC membrane showed a good growth inhibition of Staphylococcus aureus (92%) and revealed a smooth morphology, with no relevant bead formations and diameters ranging from 68 to 131 nm. The ultrafiltration abilities of the membrane containing PVA/PC were tested in a dead-end high-pressure cell (4 bar) using a reactive dye in distilled water and seawater. After 5 cycles, a maximum rejection of ≈ 85% with an average flux rate of 70 L m-2 h-1 for distilled water and ≈ 64% with an average flux rate of 62 L m-2 h-1 for seawater were determined with an overall salt rejection of ≈ 5%.